Puritan, Moderate, and Liberal Youth Muslim: Islamic Identity Typology Among Generation Z Students in Indonesian Universities - Nadri Taja; Arif Hakim; Asep Dudi Suhardini; Riyandi Baehaqi; Muhamad Imam Pamungkas (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2024)
The objective of this article is to examine the categorization of student’s comprehension of religion within two Indonesian universities, namely Universitas Islam Bandung and Universitas Pendidikan Indonesia, due to the presence in promoting Islamic values by offering Islamic religious education subject and religious mentoring programs in the curriculum that have a significant impact on student’s religious beliefs. The research employed a cross-sectional survey with descriptive analysis and utilized a sample of 139 students from both universities. It identified three typologies of Islamic identities within the students: first, the Puritans, who are identical to the Indonesian Salafist local leader Yazid bin Abdul Qadir Jawas; second, the moderate Islam, influenced by Yusuf al-Qardhawi's teaching; and third, the liberal, associated with Ulil Abshar Abdala's Jaringan Islam Liberal movement. The findings are: The students enrolled in the Islamic Religious Education at Universitas Islam Bandung showed a predominant inclination towards the Puritans (50-53.3%), the moderate (30%), and the liberal (16.7-20%), respectively. Within Universitas Pendidikan Indonesia's student reveals a trend towards the Puritans (30-43.3%), the moderate (26.7- 50%), and the liberal (20-30%), respectively. This shows there is a strong inclination towards the Puritans within both universities, and it is recommended that both universities formulate policies and strategies for strengthening religious moderation.